The mystical union in Sufism and Christian mysticism - Arifka, Angga (Edinost in dialog, 2025)
Mystical experience illustrates a fundamental aspect of human relations with the ultimate reality within the framework of religiosity. This article explores the mystical experiences of Hallaj and Meister Eckhart, both of whom came from different religious traditions. Employing a hermeneutic approach, this article attempts to read the experiences of both mystics by interpreting one with the other. Inevitably, although both mystics use different religious language and symbols, there is a strong resonance that allows us for inter-experiential reading of such mystical experiences. This article argues that mystical experience can be the strong basis of interreligious dialogue wherein although each mystical experience is personal and subjective in nature, there is something foundational that can be found as a pulse that is connected and can explain each other, rendering our interreligious understanding richer and more profound.
Keywords: Eckhart’s mystical experience; Eckhartova mistična izkušnja; fusion of mystical experiences; Hallaj’s mystical experience; Hallajeva mistična izkušnja; inter-experiential dialogue; interreligious dialogue; medizkustveni dialog; medverski dialog; poj mističnih izkušenj